The effect of Benson relaxation training on the severity of nausea and vomiting in pregnant women - Zahra Jadidi; Farideh Kazemi; Arezoo Shayan; Soodabeh Aghababaei (Mashhad University of Medical Sciences, 2021)
Introduction: Nausea and vomiting are common complaints of women during pregnancy.Relaxation is a set of neuromuscular exercises that can be used as a non-pharmacological treatment for nausea and vomiting in pregnancy.This study was performed with aim to determine the effect of Benson relaxation on the severity of nausea and vomiting in pregnant women referred to the comprehensive health centers in Hamadan. Methods: This controlled clinical trial with pre-test-post-test design was performed in 2019 on 100 primigravida women with 6-10 weeks of gestational age referred to the comprehensive health centers in Hamadan. The subjects were randomly divided into two groups of intervention and control (n=50 in each group). PUQE-24 questionnaire was completed for both groups before the intervention. The intervention group, in addition to routine pregnancy care, received relaxation techniques for 4 weeks. At the end of 4 weeks, the subjects in the intervention and control groups completed the questionnaire again. Data analysis was performed using stata (software 13) and Chi-square, Fisher's exact, Wilcoxon and Mann-Whitney. P<0.05 was considered statistically significant. Results: The mean score of nausea and vomiting before the intervention was not significantly different between the intervention and control groups (P>0.05). The mean scores of nausea and vomiting in the intervention group before and after the intervention decreased from (8.30±1.60) to (5.30±2.65) which was statistically significant (P<0.001), also changed from (8.38±1.51) to (7.39±1.70) in the control group and this difference was statistically significant (P=0.01). After the intervention, the severity of nausea and vomiting in the intervention group was significantly lower than the control group and the difference was statistically significant (P<0.001). Conclusion: Considering the effect of Benson's relaxation on reducing nausea and vomiting in pregnancy, its training is recommended for all pregnant women in the first trimester of pregnancy.